The Underlying Pathology of Autoimmune Thyroid Disease is Il-22 Independent - Hamad, Hadi H.; Raziq, Amir H. (Science Journal of University of Zakho, 2020)
The thyroid gland is frequently associated with autoimmune disease. It produces thyroid hormones responsible for controlling cellular metabolism. The current case control study involved ninety subjects which were assigned into two equal-numbered groups of patients and apparently healthy controls. For laboratory evaluation, five millilitres of venous blood were withdrawn from individual participants, serum were collected and stored at –20 oC to be analysed. Immunoassay technique was used to measure the serum level of thyroid stimulating hormone (TSH), thyroxine (T4), and triiodothyronine (T3). While ELISA technique was used for measuring the serum levels of anti-thyroid peroxidase (anti-TPO) antibodies and IL-22. The results of the current study showed that, in the patient group, thirty eight (84.44 %) subjects were diagnosed with hypothyroidism, represented by thirty five female (77.77 %) and three male (6.67 %); furthermore, seven individuals (15.56 %) were grouped as hyperthyroid patients and represented by five females (11.11 %) and two males (4.45 %). The results also demonstrated that the serum TSH levels (12.04 ± 2.76) for the patients were significantly (p< 0.05) higher than that of the control group (1.87 ± 0.15). Whereas, T3 and T4 mean serum levels ± SE were 2.05 nmol/l ±0.14; 100.66 nmol/l ± 4.76 and 2.14 nmol/l ± 0.07; 105.37 nmol/l ± 2.92 for patient and control categories, respectively. The findings of this work showed that mean serum level (IU/ml) of anti-thyroidperoxidase antibody in patient group differed significantly (P <0.05) in comparison to control group (represented by 259.08±59.99 and 8.71 ±1.23, respectively). No statistical difference was non-significant when comparison involved mean serum concentration levels of IL-22 for patients (157.22 ng/ml ± 24.81) and controls (157.08 ng/ml ± 24.80). In conclusion: IL-22 cannot be proposed as an essential factor participating the development and/or the progression of autoimmune thyroid disease (AITD).